Light in the East : AD 1000-1100 - Time-Life Books (Amsterdam : Time-Life Books, 1991)
1. World History--AD 1000-1100
Includes bibliographical references.
Bibliography: p. 168-170.
Basic Ed. Students
Keywords: Eleventh century